(untitled) (Federal University Gusau Faculty of Education Journal, 2025)
The rapid integration of Artificial Intelligence (AI) into decision-making processes, from financial services to law enforcement, presents complex challenges regarding accountability and liability. As AI systems increasingly operate with a degree of autonomy, determining who should bear responsibility for harm or error becomes a pressing legal and ethical concern. This paper explores these challenges within the context of Nigerian jurisprudence and Islamic legal ethics, guided by the principles of Maqasid al-Shariah. It examines how conventional legal concepts of human intent and negligence interact with the unique characteristics of algorithmic decision-making, where outcomes may arise from opaque or self-learning processes beyond direct human control. Nigerian law, traditionally rooted in human-centric liability, faces significant gaps in addressing the accountability of autonomous systems. Within this gap, Islamic ethical principles such as Amanah (trust) and Maslahah (public interest) provide a moral framework emphasizing justice, transparency, and societal welfare. The paper proposes a hybrid accountability model that combines statutory responsibility with ethical stewardship, ensuring that innovation aligns with human values and divine justice. However, integrating these legal and ethical perspectives, Nigeria can develop a contextually grounded framework for algorithmic justice one that maintains technological progress while preserving moral integrity and public trust. Ultimately, AI should serve humanity as a tool for equitable development, not as an unregulated force detached from human conscience or accountability.